2023
DOI: 10.1088/1361-6501/ad031d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the SERS application of gold films deposited on uncured polydimethylsiloxane with tunable LSPR

Ziran Ye,
Haixia Huang,
Ping Lu
et al.

Abstract: We present an approach to investigate the localized surface plasmon resonance and surface-enhanced Raman scattering of gold films deposited on uncured polydimethylsiloxane via thermal evaporation. Differing from solid substrates, the liquid surface of uncured polydimethylsiloxane can serve as an isotropic substrate on which gold atoms nucleate and disperse to form characteristic microstructures in a controlled manner. By adjusting experimental parameters during film deposition, the absorption of resonant plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Although the mineral sample was acquired as azurite, the peaks at 121, 194, and 458 cm À 1 found in the Raman-SERS analysis are associated with a quartz mineral as it can be seen in Figure a) where the mineral sample is compared with a known fragment of quartz that has the correspondent Raman bands of quart (14,1945 and 1945 cm À 1 ). SEM micrographs and EDS analysis revealed that the blue mineral is mainly composed of a heterogeneous mixture of two phases (Figure b), with copper and silicon being the two main constituents of these phases (encircled areas in Figure b).…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…Although the mineral sample was acquired as azurite, the peaks at 121, 194, and 458 cm À 1 found in the Raman-SERS analysis are associated with a quartz mineral as it can be seen in Figure a) where the mineral sample is compared with a known fragment of quartz that has the correspondent Raman bands of quart (14,1945 and 1945 cm À 1 ). SEM micrographs and EDS analysis revealed that the blue mineral is mainly composed of a heterogeneous mixture of two phases (Figure b), with copper and silicon being the two main constituents of these phases (encircled areas in Figure b).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…On the other hand, although the use of metallic nanoparticles in suspension is an alternative to generate the SERS effect, this effect can also be obtained by immobilizing nanoparticles on solid substrates. [10,14] According to this aspect, in recent years it has sought to develop removable devices that meet the objective of presenting the SERS effect, and that can be used to analyze different types of analytes without interfering with the integrity of the sample. [15,16] Immobilization of metal nanoparticles on flexible substrates such as gelatin, [17] or methylcellulose pastes, [18] the use of organic polymer-based substrates such as poly(vinyl pyridine) to deposit silver nanoparticles, [19] or poly(vinyl pyrrolidone) to deposit gold nanoparticles, [20] and more recently the use of poly(dimethyl siloxane) (PDMS) to immobilize AgNPs [21,22] are some promising alternatives developed that could achieve such a goal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Raman signals are characteristically weak. To amplify weak Raman signals, the surface-enhanced Raman scattering (SERS) technique is applied [5], which greatly enhances the Raman signal when the sample molecules on the surface of rough precious metals are in the range of several nanometers. Two methods are used to detect nitrites and nitrates in water using SERS: indirect and direct [6,7].…”
Section: Introductionmentioning
confidence: 99%